2020
DOI: 10.7717/peerj.8306
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic profiles of II YOU 838 (Oryza sativa) provide insights into heat stress tolerance in hybrid rice

Abstract: Heat stress is an increasing threat to rice production worldwide. To investigate the mechanisms of heat tolerance in hybrid rice and their contributions to rice heterosis, we compared the transcriptome of the hybrid rice II YOU 838 (II8) with the transcriptomes of its parents Fu Hui 838 (F8) and II-32A (II3) after heat stress at 42 °C for 0 h, 24 h, 72 h and 120 h. We also performed a proteomic analysis in II8 after heat stress at 42 °C for 24 h. The transcriptome data revealed time-dependent gene expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…The finding that JAs could alleviate spikelet‐opening impairment caused by HT stress during anthesis of PTSGMS lines would have great significance in the production of “two‐line‐method” hybrid rice. Firstly, it is an important strategy to breed and select a heat tolerant rice cultivar or a line to cope with the increasing hazard of HT stress to rice production (Karwa et al., 2020; Luo & Lau, 2019; Wahab, Akkareddy, Shanthi, & Latha, 2020; Wang et al., 2020). A higher level of JA or MeJA in the lodicules under HT stress could be used as a criterion, at least as a physiological trait, for breeding and selecting a heat tolerant rice cultivar especially a PTSGMS rice line.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that JAs could alleviate spikelet‐opening impairment caused by HT stress during anthesis of PTSGMS lines would have great significance in the production of “two‐line‐method” hybrid rice. Firstly, it is an important strategy to breed and select a heat tolerant rice cultivar or a line to cope with the increasing hazard of HT stress to rice production (Karwa et al., 2020; Luo & Lau, 2019; Wahab, Akkareddy, Shanthi, & Latha, 2020; Wang et al., 2020). A higher level of JA or MeJA in the lodicules under HT stress could be used as a criterion, at least as a physiological trait, for breeding and selecting a heat tolerant rice cultivar especially a PTSGMS rice line.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomics includes the functional genome of living organisms dealing with the total number of transcripts, their abundance in a specific cell, and posttranscriptional modifications [90,136]. Transcriptomic studies have been conducted by several technologies, including RNA sequencing, a hybridization-based approach, and other sequencing applications (Table 2).…”
Section: Transcriptomics: What Is Happening At the Transcript Level?mentioning
confidence: 99%
“…Transcriptome analysis of hybrid rice was conducted under HS (42 C) and revealed 4016, 3073, and 3596 deferentially expressed genes (DEGs) that are involved in metabolic and TF activities, regulate signal transduction and photosynthesis [90]. Clusters of genes were exhibited according to their expression, which mainly involved thermotolerance against HS.…”
Section: Transcriptomics: What Is Happening At the Transcript Level?mentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, leaves play an important role in adaptive strategies to overcome heat stress. For example, several studies in rice leaves observed differential expression of transcripts and proteins of dozens of genes upon heat shock [ 19 , 20 , 21 , 22 , 23 ]. Shi et al [ 23 ] also demonstrated that high night temperature treatment did not cause any loss in rice spikelet fertility, whereas it caused a significant decline in overall plant biomass that ultimately resulted in yield and grain quality losses.…”
Section: Introductionmentioning
confidence: 99%